Currency Substitution in Egypt and the Yemen Arab Republic : A Comparative Quantitative Analysis. (IMF Working Papers; Working Paper, 1987)
The paper provides an empirical analysis of the determinants of currency substitution in Egypt and the Yemen Arab Republic over the period 1980-86. During this period, residents have exhibited a marked preference to substitute foreign money balances for domestic balances, as indicated by their holdings of foreign currency deposits. This preference reflects changes in the expected relative returns to, and liquidity of, holdings of foreign balances. Such changes, in turn, are shown to result from intensified financial and economic imbalances, increased political uncertainties, and changes in institutional factors which affect domestic channels for acquiring and using foreign exchange resources.